PERAN DAN MAKNA SUMBANGAN DALAM MASYARAKAT PEDESAAN JAWA - Pande Made Kutanegara (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2002)
Every society collectively develops a certain system or institution which can be used to solve various problems in their life. The rural Javanese society has developed an activity to assist one another, either in the form of service, goods or money. This kind of activity is a social security system that is very important to them. This activity holds two meanings. First, it is a tool to reduce the burden of others, and the second is it creates and enhances the social solidarity of the group. In this context, helping one another has changed the feeling of insecurity to security among group of people. During a social, economic, and cultural transformation process in the Javanese rural areas, it turns out that this model of assisting one another is not always successful. On the contrary, it has created the feeling of insecurity among groups in society, especially the poor.